2011
DOI: 10.1016/j.foodchem.2010.07.087
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain from pineapple stem in alcoholic–acidic buffers for wine application

Abstract: a b s t r a c tBromelain from pineapple stem has been studied in unexplored model wine buffer (pH 3.2 tartaric acid and ethanol) in order to evaluate its applicability for white wine protein stabilization.Bromelain proteolytic activity was studied against several synthetic peptide substrates in McIlvaine buffer covering a wide pH range. Among different synthetic substrates, Bz-Phe-Val-Arg-pNA turned out to be the most suitable one to test bromelain activity at the average minimum pH value of wine (3.2). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…In addition, both enzymes had broad specificities, with ZPVANA being most susceptible and ZANPE being the least susceptible. The optimum pH of 8 observed for ZPVANA and ZAANA substrates is similar to that reported by Benucci, et al [22] on stem bromelain. However, the authors obtained higher specific activities with ZAANA instead of ZPVANA.…”
Section: Activity Of Bromelain At Various Ph and Temperaturesupporting
confidence: 89%
“…In addition, both enzymes had broad specificities, with ZPVANA being most susceptible and ZANPE being the least susceptible. The optimum pH of 8 observed for ZPVANA and ZAANA substrates is similar to that reported by Benucci, et al [22] on stem bromelain. However, the authors obtained higher specific activities with ZAANA instead of ZPVANA.…”
Section: Activity Of Bromelain At Various Ph and Temperaturesupporting
confidence: 89%
“…Bromelain is also useful in industrial biotechnology, especially in winemaking, since it prevents the formation of unwanted protein precipitates after the wine is bottled. 69 Esti et al 70 studied the effect of wine inhibitors (ethanol, sulfur dioxide, grape skin, and seed tannins) on the activity of stem bromelain covalently immobilized on chitosan beads. The results obtained showed that immobilized stem bromelain might have potential biotechnological applications in winemaking, since this enzyme is capable of stabilizing proteins in wine.…”
Section: Applicationsmentioning
confidence: 99%
“…For these reasons, alternative methods for white wine stabilization have been extensively investigated. A variety of alternatives has been proposed, ranging from the use of other adsorbents (Cabello-Pasini, Victoria-Cota, Macias-Carranza, Hernandez-Garibay, & Muñiz- Salazar, 2005;de Bruijn et al, 2009;Salazar, Achaerandio, Labbe, Guell, & Lopez, 2006;Sarmento, Oliveira, & Boulton, 2000;Vincenzi, Polesani, & Curioni, 2005), ultrafiltration (Hsu et al, 1987), flash pasteurization (Pocock, Høj, Adams, Kwiatkowski, & Waters, 2003) and proteases (Benucci, Liburdi, Garzillo, & Esti, 2011;Waters, Wallace, & Williams, 1992), but none has proven sufficiently effective to replace bentonite.…”
Section: Introductionmentioning
confidence: 99%